Potential role of CYP2D6 in the central nervous system. (November 2013) - Cheng, Jie; Zhen, Yueying; Miksys, Sharon; Beyoğlu, Diren; Krausz, Kristopher W.; Tyndale, Rachel F.; Yu, Aiming; Idle, Jeffrey R.; Gonzalez, Frank J.
Abstract 1. Cytochrome P450 2D6 (CYP2D6) is a pivotal enzyme responsible for a major drug oxidation polymorphism in human populations. Distribution of CYP2D6 in brain and its role in serotonin metabolism suggest that CYP2D6 may have a function in the central nervous system. 2. To establish an efficient and accurate platform for the study of CYP2D6 in vivo, a human CYP2D6 (Tg-2D6) model was generated by transgenesis in wild-type (WT) C57BL/6 mice using a P1 phage artificial chromosome clone containing the complete human CYP2D locus, including the CYP2D6 gene and 5′- and 3′-flanking sequences. 3. Human CYP2D6 was expressed not only in the liver but also in the brain. The abundance of serotonin and 5-hydroxyindoleacetic acid in brain of Tg-2D6 is higher than in WT mice, either basal levels or after harmaline induction. Metabolomics of brain homogenate and cerebrospinal fluid revealed a significant up-regulation of L-carnitine, acetyl-L-carnitine, pantothenic acid, 2′-deoxycytidine diphosphate (dCDP), anandamide, N-acetylglucosaminylamine and a down-regulation of stearoyl-L-carnitine in Tg-2D6 mice compared with WT mice. Anxiety tests indicate Tg-2D6 mice have a higher capability to adapt to anxiety. 4. Overall, these findings indicate that the Tg-2D6 mouse model may serve as a valuable in vivo tool to determine CYP2D6-involved neurophysiological metabolism and function.